Transformasi Literasi Digital Guru Sekolah Dasar melalui Program Upskilling Penggunaan Canva for Education dan Gemini AI - Widiyanti Widiyanti; Nunung Nurjanah; Lismi Animatul Chisbiyah; Muhammad Idris Effendi; Septa Eka Nurianto Putra; Pinky Kusuma Ningtyas (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
This community engagement program was implemented to enhance the digital literacy of elementary school teachers at SDN Wonosari 2, Pagu Subdistrict, Kediri Regency through training on Canva for Education and Gemini AI. The program addressed critical issues such as low digital literacy, limited use of digital learning media, and the absence of a digital mindset among teachers. The implementation included hands-on training over two days and intensive mentoring for two weeks, accompanied by pre- and post-tests, product observations, and satisfaction questionnaires. The results demonstrated significant improvements in teachers’ technical skills, a more open attitude toward technology integration, and the formation of internal digital collaboration groups. This program proved to be relevant and practical in bridging the digital literacy gap among elementary teachers and has strong potential to be replicated as a sustainable community service model for other primary schools facing similar challenges.